IMPLEMENTASI PROGRAM VISIT JAWA TENGAH (VJT) 2013 PADA DINAS KEBUDAYAAN DAN PARIWISATA PROVINSI JAWA TENGAH - Fendhi Hermawan; kushandayani .; Puji Astuti (Journal of Politic and Government Studies, 2015)
ABSTRACT VISIT CENTRAL JAVA PROGRAM IMPLEMENTATION IN 2013 AT CENTRAL JAVA PROVINCIAL CULTURE AND TOURISM OFFICEBy Fendhi Hermawan  Visit Central Java in 2013 designed as an attempt to become the point of cultural revival and tourism central java in Indonesia and the worlds eyes. It was an attempt to accelerate the development of culture and tourism in the province of central java. And targeting tourist visit as many twenty five million local tourist and five hundred thousand foreign tourists. Visit Central Java in 2013 aims to make tourism as a central java acceleration for sustainability development potential, economic, cultural, social, and better known by the people of Indonesia and the world. Visit Central Java in 2013 also aims to realize the vision of central java as a cultural center and a major tourist destination, both for local tourists or foreign tourists. The approach used in this research is descriptive research method with the type of research is a case study, which is an approach that reviewers directed to the case of intensive, in-depth and detailed and comprehensive. With this study means that the researchers tried to describe in detail a phenomenon or situation actually happened on the efforts undertaken by the Government of the Province of Central Java in the course of the Visit Central Java in 2013. These results indicate that the initial target has been specified in the Visit Central Java is 25,500,000 tourists. Both foreign tourists and domestic tourists are expected to visit a tourist attraction and tourism events in Central Java. With details of 25 million people local tourists and 500,000 foreign tourists. Based on these targets visit Central Java program implementation in 2013 has reached or even exceeded the initial target has been declared. In 2013 the number of visitors to various tourist attraction and tourist events as much as 29,818,752 tourists, both foreign tourists and domestic tourists. It has been shown that the initial target of 25.5 million tourists have been achieved even have exceeded the initial target. This amount consists of 29,430,609 domestic tourists as people who exceed the initial target of 25 million people. Although the initial target amount has been reached. However, for the number of visitors from foreign tourists do not reach the initial target of 500,000 people. For visitors from foreign tourists just as much as 388 143 people.              Keywords: Implementation, Program, Visit Central Java